Language in literature style and foregrounding - Leech, Geoffrey (Routledge, 2013)
Over a period of over forty years, Geoffrey Leech has made notable contributions to the field of literary stylistics, using the interplay between linguistic form and literary function as a key to the?mystery' of how a text comes to be invested with artistic potential. In this book, seven earlier papers and articles, read previously only by a restricted audience, have been brought together with four new chapters, the whole volume showing a continuity of approach across a period when all too often literary and linguistic studies have appeared to drift further apart.